The lost world of scripture : ancient literary culture and biblical authority - Walton, John H., 1952-; Sandy, D. Brent, 1947- (Downers Grove, Illinois : IVP Academic, an imprint of InterVarsity Press, 2013)
'From Dr. John H. Walton, author of the bestselling The Lost World of Genesis One, and Dr. D. Brent Sandy, author of Plowshares and Pruning Hooks, comes a detailed look at the origins of Scriptural authority in ancient oral cultures and how it informs our understanding of the Old and New Testaments today. Stemming from questions about Scriptural inerrancy, inspiration and oral transmission of ideas, The Lost World of Scripture examines the process by which the Bible has come to be what it is today. From the reasons why specific words were used to convey certain ideas to how oral tradition impacted the transmission of Biblical texts, the authors seek to uncover how these issues might affect our current doctrine on the authority of Scripture.'In this book we are exploring ways God chose to reveal his word in light of discoveries about ancient literary culture,' write Walton and Sandy. 'Our specific objective is to understand better how both the Old and New Testaments were spoken, written and passed on, especially with an eye to possible implications for the Bible's inspiration and authority'' -- Publisher description.
IV. Concluding affirmations on the origin and authority of scripture : Proposition 18: Affirmations about the origin of scripture confirm its fundamental oral nature ; Proposition 19: Affirmations about the authority of scripture asserts its divine source and illocution ; Proposition 20: Inerrancy has essential roles and limitations ; Proposition 21: Belief in authority not only involves what the Bible is but also what we do with it.
Includes bibliographical references and indexes.
Keywords: Bible -- Evidences, authority, etc; Bible and tradition; Oral communication; Oral tradition; Transmission of texts